Forage and grain yields of barley, wheat and oats - Bolsen, K.; Moore, W. (Kansas State University. Agricultural Experiment Station, 2011)
Interest in small cereal grain silages for beef cattle has increased in recent years. Two years' research at this station (Prog. Rpt. 262) has shown: (1) winter barley and winter wheat had similar forage yields and (2) forage yields were highest in the dough stage of plant growth and lowest in the boot stage. In this trial, we continued to measure effects of type and variety of cereal grain on forage and grain yields.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Forage yield; Grain yield; Barley; Wheat; Oats